Bases, Models and Some Tools For Implementation of Online Teaching in Interactivity - Diep, Phương Chi; Hoang, Anh (Journal of Technical Education Science, 2023)
Online teaching is a way of organizing teaching and learning based on web as well as on digital applications/ tools to create a virtual learning environment with distance learning to achieve certain learning goals. Besides the advantage of helping learners overcome geographical barriers in learning, Online teaching also has the limitation of transaction distance, ie distance in remote communication between teacher and learners, between learners and learners, which mades the organization of teaching and learning difficult. In particular, the difficulty of the lack of interaction - which is easily achieved through traditional face-to-face classes - is one of the biggest. The article discusses the basis to design and implement the Online teaching in the direction of increasing the interaction and shares some tools/ techniques to improve the efficiency of online teaching and learning on the basis of analyzing the relevant theoretical bases and synthesizing experience from practice.